Peran Dukungan Orang Tua dalam Meningkatkan Motivasi Belajar Siswa Pendidikan Menengah - Rani Puspita; Silvina Waroh; Gusmaneli (Journal Educational Research and Development | E-ISSN : 3063-9158, 2024)
Parental support has a significant impact on children's learning achievement and character formation. This research examines various aspects of parental support, from improving academic outcomes to developing children's social and emotional skills. Results show that parental involvement in children's education, both emotionally and financially, contributes to children's positive attitudes towards learning and reduces the risk of dropping out of school. Apart from that, parental support also plays an important role in developing moral values, empathy, independence and emotional management, which shape the child's overall character. However, many parents face challenges, such as time constraints, economic pressures, and lack of knowledge, which can hinder their ability to provide optimal support. Therefore, it is important for parents to seek sources of support and information to increase their role in their child's education. This research emphasizes the need for collaboration between parents, schools and the community to support children's development optimally.